Exploitation of aesthetic capital - disapproved by whom? - Iida Kukkonen; Erica Åberg; Outi Sarpila; Tero Pajunen (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose The purpose of this paper is to investigate the gendered double standards of exploiting physical appearance in Finland. Drawing from literature on physical appearance as a form of capital, four hypotheses on role of gender in endorsing double standards are put forth, and then empirically tested. The focus is on whether women or men are more disapproving of women exploiting their appearance. The paper also explores whether self-perceived attractiveness has an influence on the gendered endorsement of double standards.Design/methodology/approach The study utilises unique survey data with a split-ballot design to study gendered double standards at a societal level by means of ordered logistic regression. The data are nationally representative of 15-74-year-old Finns (n=1,600).Findings The main finding is that women are more prone to endorse the double standards against each other. It is particularly women who do not perceive themselves as attractive who are likely to hold double standards. Experienced unattractiveness is associated with disapproving attitudes towards the exploitation of physical appearance-related assets for both women and men. Men are overall more approving compared to women, and do not generally hold double standards.Originality/value Research on double standards in different spheres of life in a relatively gender equal country like Finland gives an intriguing example of gendered social inequality. The information provided by this paper deepens our understanding of gendered social stratification related to physical appearance.